Mike's mystery - Warner, Gertrude Chandler, 1890-1979 (Warner, Gertrude Chandler, 1890-1979. Boxcar children mysteries, 2023)
"The Alden children meet Mike Wood and a strange chain of events begins. Mike's house is mysteriously burned down, a man in a blue hat appears, and the Alden's uranium mine is in danger of being sabotaged. The four children solve the mystery." --